Policy Advocacy Training for Women Victims of Violence in Maros Regency - Muh Tang Abdullah; Andi Ahmad Yani; Atta Irene Allorante; Amril Hans (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Cases of violence against women in Maros Regency are quite high. For example, in 2016, according to Department of Women Empowerment and Child Protection (DP3A) data, there were 68 cases and 21 police data cases. Likewise, divorce data in the Religious Courts are more caused by domestic violence. Of course, this social problem must be immediately addressed through local government policies. However, in fact, no policy specifically regulates the handling of this problem. Therefore, community service in the form of policy advocacy training for village women victims of violence needs to be carried out. This advocacy training was attended by 25 participants from various villages. Participants were provided with policy advocacy materials covering (1) government policies and programs on the protection of women; (2) the concept and practice of policy advocacy; (3) issues of violence and protection of women; (4) technical public speaking and lobby strategy, and (5) public opinion and press release materials. The results of the training evaluation resulted in an increase in knowledge and skills for participants after following the entire set of materials provided. Recommendations for activities are suggested to immediately take more concrete action in the form of policy advocacy to encourage the issuance of the Regional Regulation (Perda) of Maros Regency concerning Protection of Women from Violence